Antibiotics Study of Antibiotic use patterns in pediatric pneumonia patients at Kediri Hospital: PENUMONIA - Wardhani, Dita Kusuma; Anggi Restyana; Fidi Setyawan; Janik Kurniawati (Universitas STRADA Indonesia, 2025)
Pneumonia is an acute infection of the lung parenchyma, consisting of alveoli and interstitial tissue on chest X-ray. The purpose of this study was to identify the pattern of antibiotic use in pneumonia patients and obtain accurate data on antibiotic use in pneumonia patients and also analyze the results of data collection on antibiotic use and the rationality of antibiotic use. This type of research is descriptive qualitative, the sample of this study were pediatric patients aged 1 year to 5 years who were diagnosed with pneumonia from 2018-2023 at the Hospital in Kediri City. The results of the study obtained the age of pneumonia patients at most at the age of 2 months - 1 year as many as 24 children, most pneumonia sufferers were male, obtaining 22 children. Overall, this study obtained rational results in the analysis of the quality of antibiotic use.